On the determination of reference levels for quality assurance of flattening filter free photon beams in radiation therapy. Issue 2 (15th January 2014) - Clivio, Alessandro; Belosi, Maria Francesca; Cozzi, Luca; Nicolini, Giorgia; Vanetti, Eugenio; Bolard, Grégory; Fenoglietto, Pascal; Krauss, Harald; Fogliata, Antonella
Abstract : Purpose: : New definitions for some dosimetric parameters for use in quality assurance of flattening filter free (FFF) beams generated by medical linear accelerators have been suggested. The present study aims to validate these suggestions and to propose possible reference levels. Methods: : The main characteristics of FFF photon beams were described in terms of: field size, penumbra, unflatness, slope, and peak‐position parameters. Data were collected for 6 and 10 MV‐FFF beams from three different Varian TrueBeam Linacs. Measurements were performed with a 2D‐array (Starcheck system from PTW‐Freiburg) and with the portal dosimetry method GLAaS utilizing the build‐in portal imager of TrueBeam. Data were also compared to ion chamber measurements. A cross check validation has been performed on a FFF beam of 6 MV generated by a Varian Clinac‐iX upgraded to FFF capability. Results : : All the parameters suggested to characterize the FFF beams resulted easily measurable and little variation was observed among different Linacs. Referring to two reference field sizes of 10 × 10 and 20 × 20 cm 2, at SDD = 100 cm and d = dmax, from the portal dosimetry data, the following results (averaging X and Y profiles) were obtained. Field size: 9.95 ± 0.02 and 19.98 ± 0.03 cm for 6 MV‐FFF (9.94 ± 0.02 and 19.98 ± 0.03 cm for 10 MV‐FFF). Penumbra: 2.7 ± 0.3 and 2.9 ± 0.3 mm for 6 MV‐FFF (3.1 ± 0.2 and 3.3 ± 0.3 for 10 MV‐FFF). Unflatness: 1.11 ± 0.01 and 1.25 ± 0.01 for 6 MV‐FFF (1.21 ± 0.01 and 1.50 ± 0.01 for 10 MV‐FFF). Slope: 0.320 ± 0.020%/mm and 0.43 ± 0.015%/mm for 6 MV‐FFF (0.657 ± 0.023%/mm and 0.795 ± 0.017%/mm for 10 MV‐FFF). Peak Position −0.2 ± 0.2 and −0.4 ± 0.2 mm for 6 MV‐FFF (−0.3 ± 0.2 and 0.7 ± 0.3 mm for 10 MV‐FFF). Results would depend upon measurement depth. With thresholds set to at least 95% confidence level from the measured data and to account for possible variations between detectors and methods and experimental settings, a tolerance set of: 1 mm for field size and penumbra, 0.04 for unflatness, 0.1%/mm for slope, and 1 mm for peak position could be proposed from our data. Conclusions : : The parameters proposed for the characterization and routine control of stability of profiles of FFF beams appear to be a viable solution with a strong similarity to the conventional parameters used for flattened beams. The results from three different TrueBeams and the cross‐validation against a Clinac‐iX suggested the possible generalization of the methods and the possibility to use common tolerances for the parameters. The data showed also the reproducibility of beam characteristics among different systems (of the same vendor) and the resulting parameter values could therefore be possibly generalized.